Estimating biomass carbon stocks for a Mediterranean forest in central Spain using LiDAR height and intensity data - García, Mariano; Riaño, David; Chuvieco, Emilio; Danson, F. Mark; García, Mariano; Riaño, David; Chuvieco, Emilio; Danson, F. Mark (REMOTE SENSING OF ENVIRONMENT, 2010)
Biomass fractions (total aboveground, branches and foliage) were estimated from a small footprint discrete-return LiDAR system in an unmanaged Mediterranean forest in central Spain. Several biomass estimation models based on LiDAR height, intensity or height combined with intensity data were explored. Raw intensity data were normalized to a standard range in order to remove the range dependence of the intensity signal. In general terms, intensity-based models provided more accurate predictions of the biomass fractions. Height models selected were mainly based on a percentile of the height distribution. Intensity models selected included variables that consider the percentage of the intensity accumulated at different height percentiles, which implicitly take into account the height distribution. The general models derived considering all species together were based on height combined with intensity data. These models yielded R(2) values greater than 0.58 for the different biomass fractions considered and RMSE values of 28.89, 18.28 and 1.51 Mg ha(-1) for aboveground, branch and foliage biomass, respectively. Results greatly improved for species-specific models using the main species present in each plot, with R(2) values greater than 0.85, 0.70 and 0.90 for black pine, Spanish juniper and Holm oak, respectively, and with lower RMSE for the biomass fractions. Reductions in WAR point density had only a small effect on the results obtained, except for those models based on a variation of the Canopy Reflection Sum, which was weighted by the mean point density. Based on the species-specific equations derived, Holm oak dominated plots showed the highest average carbon contained by aboveground biomass and branch biomass 44.66 and 31.42 Mg ha(-1) respectively, while for foliage biomass carbon, Spanish juniper showed the highest average value (3.04 Mg ha(-1)). (C) 2009 Elsevier Inc. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 360 PARK AVE SOUTH, NEW YORK, NY 10010-1710 USA publisher: ELSEVIER SCIENCE INC
Keywords: Biomass fractions; Carbon content; Intensity; LiDAR